Structure–function relationships for Schizophyllum commune trehalose phosphorylase and their implications for the catalytic mechanism of family GT-4 glycosyltransferases - Goedl, Christiane (Portland Press Ltd., 2006)
The cDNA encoding trehalose phosphorylase, a family GT-4 glycosyltransferase from the fungus Schizophyllum commune, was isolated and expressed in Escherichia coli to yield functional recombinant protein in its full length of 737 amino acids. Unlike the natural phosphorylase that was previously obtained as a truncated 61 kDa monomer containing one tightly bound Mg(2+), the intact enzyme produced in E. coli is a dimer and not associated with metal ions [Eis, Watkins, Prohaska and Nidetzky (2001) Biochem. J. 356, 757–767]. MS analysis of the slow spontaneous conversion of the full-length enzyme into a 61 kDa fragment that is fully active revealed that critical elements of catalysis and specificity of trehalose phosphorylase reside entirely in the C-terminal protein part. Intact and truncated phosphorylases thus show identical inhibition constants for the transition state analogue orthovanadate and α,α-trehalose (K(i)≈1 μM). Structure-based sequence comparison with retaining glycosyltransferases of fold family GT-B reveals a putative active centre of trehalose phosphorylase, and results of site-directed mutagenesis confirm the predicted crucial role of Asp(379), His(403), Arg(507) and Lys(512) in catalysis and also delineate a function of these residues in determining the large preference of the wild-type enzyme for the phosphorolysis compared with hydrolysis of α,α-trehalose. The pseudo-disaccharide validoxylamine A was identified as a strong inhibitor of trehalose phosphorylase (K(i)=1.7±0.2 μM) that displays 350-fold tighter binding to the enzyme–phosphate complex than the non-phosphorolysable substrate analogue α,α-thio-trehalose. Structural and electronic features of the inhibitor that may be responsible for high-affinity binding and their complementarity to an anticipated glucosyl oxocarbenium ion-like transition state are discussed.